Islamic Curriculum: Philosophical Foundations and Historical Practices - Ramdane, Tahraoui; Souad, Merah (2019)
There is a close relationship between the Islamic conceptualization of curriculum and the nature of the Islamic faith. An Islamic curriculum can be defined as an integrated system of constant divine facts, criteria and values, as well as changing human experiences and items of learning and skills which an Islamic academic offers to learners therein in order to enable them to attain the degree of perfection for which Allah has prepared for them. The Islamic curriculum transcends the limited space of pure religious subjects to embody every useful knowledge. Across the Islamic history one can notice that the Islamic curruculum has developed in three main stages; a. Stage of infancy and standardization coeval of prophet Muhammad message and his first four successors, b. Stage of diversity in the post classical era (661 AD to 1450 AD which could be divided into pre-madrasa and madrasa eras, c. Stage of regression and reform which stretches from the tenth century untill the present time. During this stage a number of historical, cultural, social and political contributed to the dec number of historical, cultural, social and political contributed to the decnumber of historical, cultural, social and political contributed to the dec number of historical, cultural, social and political contributed to the dec number of historical, cultural, social and political contributed to the dec number of historical, cultural, social and political contributed to the dec number of historical, cultural, social and political contributed to the dec number of historical, cultural, social and political contributed to the dec number of historical, cultural, social and political contributed to the dec number of historical, cultural, social and political contributed to the dec number of historical, cultural, social and political contributed to the decnumber of historical, cultural, social and political contributed to the decnumber of historical, cultural, social and political contributed to the dec number of historical, cultural, social and political contributed to the dec number of historical, cultural, social and political contributed to the decnumber of historical, cultural, social and political contributed to the dec number of historical, cultural, social and political contributed to the dec number of historical, cultural, social and political contributed to the dec number of historical, cultural, social and political contributed to the decline of the line of the line of the line of the Islamic curriculum and Islamic curriculum and Islamic curriculum and Islamic curriculum and Islamic curriculum and Islamic curriculum and Islamic curriculum and Islamic curriculum and Islamic curriculum and diminished its appeal. Despite current efforts to revive the Islamic curriculum, challenging issues like dualism, rigidity, passivity, irrelevancy and social alienation continue to plague this model.